PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Pabrik PTPN V Sei Rokan Kabupaten Rokan Hulu) - Yeldi Okta Saputra; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Leardership style and work environment will impact on employee performance. So to build an organization, leaders and workers must work together to achieve company goals. This study aims to determine about the influence of leadership style and working environment on the performance of the employee (Study at The PTPN V Vice Factory Rokan Hulu District). Styles leadership as a variable (X1), the work environment as a variable (X2) and employee performance as (Y).The method in this research is descriptive and quantitative using SPSS 17, wherein the samples used are permanent employees at The PTPN V Vice Factory Rokan Hulu District by respondents as many as 62 peoples. The formula used to determine the sample slovin, as well as a sampling technique by means of probability sampling include. Data collection through questionnaires and interview. Results so it can be know that the leadership style variable have a significant effect on the performance of employees, the working environment have a significant effect on employee performance, and significant relationship between the leadership style and work environment on employee performance. Keywords: Leadership Style, Work Environment, Employee Performance